Implementing Character Education through Habituation Activities in Elementary Schools - Marita Lailia Rahman; Dianis Izzatul Yuanita (LPPM STAI Muhammadiyah Probolinggo, 2026)
Character education must be instilled from an early age in children. the formation of character in children begins while they are still in the womb, until they are born and grow up in their surrounding environment. The roles of those closest to them greatly influence a child’s character, including the parenting roles of parents, teachers, and the people in the child’s developmental environment. The scope of the study is about the implementation of character program that applied to students, the character values produced, and the character evaluations which was conducted at SD Plus Rahmat Kota Kediri. This research used qualitative method by using data collection techniques of interview, observation, and documents, with the model analysis interactive techniques. The Novelty of this research is the character habituation program implemented during intra-curricular, co-curricular, and extra-curricular activities. The values of character that are implemented include religiousness, curiosity, social care, discipline, and creativity. The evaluation is conducted by holding tiered class meetings and teacher training workshop programs. This research is expected to serve as a source of reference and study for the application of practices related to character habituation among students, also becomes an alternative policy applied in schools related to the character building program of students.